Feasibility study on detecting lung tumour in multilayer thorax model using ultra-wideband microwave imaging - Babarinde, Oluwatosin John (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2015)
In recent times however, microwave imaging techniques are being proposed for detection of various forms of cancer. The detection of cancer using microwaves in the frequency range of 300 MHz to 30 GHz is possible iin the premise that the dielectric properties of tumour tissues are different from the normal host tissues. These contrasts in dielectric properties are being explored in microwave tomography, ultra-wideband (UWB) microwave imaging radar, radiometry, and thermo-acoustic tomography. This thesis presents a study in using confocal microwave imaging technique which itself is a form of the UWB microwave imaging radar to detect millimetre sized tumour in the human lungs. The detection system comprises of a human thorax modelled as multilayer tissues of lung, bone, muscle, fat and skin; a 10 mm tumour; a UWB antenna connected to a vector network analyser; and a proposed modified delay and sum(mDAS)imaging algorithm for signal processing and image reconstruction purposes. Reconstructed microwave images show the possibility of detecting tumours in lung in both simulation and experimental procedures.